Isolation and Identification of New Pigment From Monascus purpureus - Anna Yuliana; Lina Rahmawati; Salsabila Adlina (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2021)
This research was aimed to isolate and identify the new pigment from the main pigments of Monascus purpureus, which derive from five different isolates and through with solid fermentation used IR-64 rice as substrate. The measurement of pigment was done by extracting t samples using methanol in the 14th day of fermentation process. The absorbance of main pigment was measured by a UV-Visible spectrophotometer at the wavelengths of 364, 365, 375, 400, 480 and 500 nm. The results showed that the absorbance of each pigments isolate varied within ranges from 0.219 to 0.559. Result followed of Thin Layer Chromatography (TLC) method with chloroform: acetone (9: 1). TLC results were followed by isolating IPB-B samples using Thin Layer Chromatography- Preparative (TLC-P), whereas the band obtained was identified by using Liquid Chromatography-Mass Spectrum (LC-MS) instrument. The isolated and identified IPB-B samples showed that there was found a new compound of Molecular Weight (MW), which was Monaphilol A with Molecular Weight (MW) of 384.47.